Microstructural, tribological and compression behaviour of Copper matrix reinforced with Graphite-SiC hybrid composites - Jamwal A.; Seth P.P.; Kumar D.; Agrawal R.; Sadasivuni K.K.; Gupta P. (My University, 2025)
Metal Matrix Composites (MMCs) are generating a wide and varied range of interest in the recently developed materials because of their high applicability in the industries. Copper matrix composites have rich properties like high thermal conductivity, high temperature resistance, high corrosion resistance and high weldability which makes them promising and demanding material for heat exchangers, electrical components and automoblies. Graphite and Silicon Carbide are the most economical reinforcements to improve the wear characteristics of pure copper. Present study concentrates on preparation of Copper-Graphite-Silicon Carbide hybrid metal matrix composite by stir casting technique. XRD analysis of composites show that there is no intermediate reaction occuring between copper and reinforcement particles. Micrographs of composites revealed the uniform distribution of reinforcement particles in copper matrix. A good interfacial bonding between Copper and Graphite-Silicon Carbide particles is found. Hardness of composites is tested by Vickers hardness tester and it is found that hardness of composites decreases with increase in graphite content. Wear tests were performed on Pin-on-Disc test rig. It is found that wear rate is decreasing with increase in reinforcement content. The maximum wear resistance is found at 8 wt% reinforcement content. Compressive strength of composites is tested using Universal testing machine and showed a decrease in value with increase in graphite content. It is spontaneously expected that present composite will be highly beneficial in structural and mechanical applications. © 2020 Elsevier B.V.